Balancing State Revenue and Fair Competition in Social Commerce Platforms - Ilham Abbas; Rizki Ramadani (Faculty of Law, Universitas Sebelas Maret, 2025)
Indonesia's growing population has contributed to the expansion of e-commerce, but state revenue stagnates. Meanwhile, social commerce platforms have created harmful rivalry, threatening MSMEs' sustainability. The study seeks to identify legal issues in social commerce platforms, including taxation and fair competition, and provide a regulatory framework that maximizes digital sector state revenue while protecting domestic firms. This study uses legal research methodology, focusing on a statutory and comparative approach. The finding reveals that insufficient tax compliance among e-commerce participants, inadequate oversight of foreign social commerce businesses, and predatory pricing practices are the main causes of structural inequality. Additionally, uneven government policies reduce domestic enterprises' competitiveness. This study recommends mandating foreign social commerce platforms to establish a permanent presence in Indonesia to comply with national tax regulations, allocating a minimum of 30% of social commerce tax revenues to empower MSMEs and support digitalization programs, implementing cross-ministerial big data monitoring for transaction oversight, and strengthening the Business Competition Supervisory Commission to combat predatory behavior. A comprehensive regulatory reform is expected to balance governmental interests, MSMEs, and the global digital economy.